Endophthalmitis after strabismus surgery: incidence and outcome in relation to age, operated eye muscle, surgical technique, scleral perforation and immune state. Issue 1 (13th June 2020) - Simonsz, Huibert J.; Rutar, Tina; Kraft, Stephen; Thiadens, Alberta A.H.J.; Batstra, Manou R.; Verdijk, Robert M.; Loeffler, Karin U.; Kommerell, Guntram; ,
Abstract : Purpose: Identify risk factors for endophthalmitis after strabismus surgery (EASS) and relate these to incidence and outcome. Methods: Ophthalmologists, who had operated, diagnosed or treated EASS, completed a case record form with 71 questions in six domains: Preoperative, Surgery, Perforation, Postoperative, Outcome and Experts' opinion. To estimate the age‐specific incidence per number of strabismus operations in the Netherlands during 1994‐2013, the age distribution of Dutch cases was compared with the age‐specific rates of strabismus surgery in the Dutch Registry of Strabismus Operations and with population data. Exploratory data analysis was performed. The immune state was evaluated in six patients. Five enucleated eyes were studied histopathologically. Results: None of the 26 patients (27 eyes with EASS) were between 9 and 65 years old, except for one patient with retinal haemorrhage followed by endophthalmitis. In the Netherlands during 1994‐2013, the rate of EASS was approximately one per 11 000 strabismus operations, but one per 4300 for children aged 0–3 and one per 1000 for patients 65 and older. Endophthalmitis was diagnosed on postoperative day 1–4 in children aged 0–3. In all 15 children aged 0–5, the 16 affected eyes were phthisical, eviscerated or enucleated. The involved eye muscle had been recessed in 25 of 27 cases. It was a medial rectus in 15 of 16 children aged 0–6. It was a lateral (6), inferior (2) or medial (1) rectus in elderly. Scleral perforation went unnoticed in all children (no record in three) and in two of seven elderly (no record in two). Histopathology showed transscleral scarring compatible with scleral perforation in four patients but, in a two‐year‐old girl who had EASS together with a transient medial rectus palsy, the sclera underneath the former suture tract was not perforated but did contain the long posterior ciliary artery. Conclusions: Endophthalmitis after strabismus surgery (EASS) affects children and elderly, with a grave outcome in young children. It occurs after recession of the medial rectus muscle in children, and it may occur without scleral perforation. Age and perforation are key determinants that interact with other factors that determine the occurrence and fulminance of EASS.